ELENA MARIA ŞORBAN – BOOK QUARTET: 1. THE HISTORY OF MUSIC AND US: CREATIVE PERMANENCIES, 2. THE OLD MUSIC. A CONCISE HISTORY, 3. CLASSICAL AND ROMANTIC MUSIC, 4. THE NEW MUSIC Eikon Publishing House, Cluj-Napoca, 2013 & 2014 - Anamaria Mădălina HOTORAN (Studia Universitatis Babeş-Bolyai. Musica)
By the end of 2013 and the beginning of 2014, Elena Maria Şorban published a book tetralogy, a comprehensive compendium covering the entire music history, from the ancient music to the contemporary creations.